The quantitative and qualitative scientific production: A bibliometric study of the five main Asian economies in R&D - Arana-Barbier, Pablo José (Malaysian Journal of Library and Information Science, 2020)
The five economies in Asia that invest the most in research and development, as a percentage of Gross Domestic Product (GDP), are Israel, South Korea, Japan, Singapore and China. Nevertheless, the results in the number of scientific output in terms of research publications, and the citations received by them, reveal a whole different reality among those countries. Furthermore, the intellectual production based on quantitative research methods used to be much more popular and defended than that on qualitative methods. However, three of these five countries mentioned trust more in the qualitative paradigm, represented by grounded theory, than in the quantitative one, represented by structural equation modeling. The current study investigates 25 years of scientific production available in the Web of Science and shows that, even though China is undoubtedly Asia’s leader in intellectual production, measured by publication productivity and scientific impact, the scientific community trusts the least on China’s papers regarding grounded theory, placing China in fifth place among the studied countries for qualitative studies, and third place for quantitative studies. The paper also deepens on the concept of trust as a replacement of impact, and projects the near future for the five studied countries regarding quantitative and qualitative intellectual production.